Estudio de las políticas públicas y su incidencia para combatir la pobreza en el Gobierno Autónomo Descentralizado Parroquial Rural de Canuto - Faubla Salazar, Ginger Pierina (2024)
The objective of this research was to analyze public policies and their effect on the fight against poverty in the rural parish of Canuto. Based on the results obtained, an action plan was proposed that integrates strategies of diagnostic processes of the reality of the population. The methodology that was applied in the techniques was the interview and the survey through the Likert scale model, in addition to the use of bibliographic and field research, which were analyzed using inductive, deductive and analytical methods. The results obtained demonstrate that the public policies used in the GAD of the Canuto parish to combat poverty are developed through various programs and agreements that the institution has signed with other government entities at the national and cantonal level and with various state portfolios. It is clear that, although several projects have been established by the institution, this is not reflected in the reality of the population because the majority is unaware of their existence. It is worth emphasizing that the identification of the results of the implementation of public policies demonstrates a generalized disagreement about whether the entity is really carrying out an effective diagnosis in the population, thus, the lack of direct contact and technical assistance by the GAD of the rural Canuto parish is a point of dissatisfaction where non-compliance with the public politics.